Detection of Clostridium difficile toxins A/B in the stool specimens from patients and medical staff of the children’s antituberculosis department - Ivanko, O. H.; Patsera, M. V.; Skrypnykova, Ya. S. (Zaporozhye Medical Journal, 2018)
The objective of our research was to determine the detection frequency of C. difficile toxins in the stool specimens from children receiving long-term treatment with rifampicin and in health care workers treating these children in a separate anti-tuberculosis hospital. Materials and methods. 139 children with the average age of 13.6 were examined; all of them had an infiltrative pulmonary tuberculosis and received long-term treatment with rifampicin at the Zaporizhzhia Regional Tuberculosis Dispensary. Also, 32 medical workers were examined and divided into high and low risk groups of C. difficile infection depending on the closeness of their contacts with children at the department. To detect C. difficile toxins A/B in the stool an ELI method was applied using the ELISA test system (Diagnostic Automation, Inc.,Calabasas,USA). The amount of toxins ranged from 1 ng and more in 1 ml of feces sample was considered as diagnostic. Results. 74 (53 %) children out of the 139 had a diagnostic titer of C. difficile toxins in their stool specimens. Among them, 49 (66 %) children had recurrent diarrhea, syndrome of abdominal pain without diarrhea was observed in 20 (27 %) and asymptomatic carrier state of CDI detected by laboratory tests was defined in 5 (7 %) children. Among 32 medical workers in the same department 6 (18.8 %) of them were positive for C. difficile toxins. It is noteworthy that three of them had received antibiotics during the last month prior to the study. Conclusions. In the context of professional contacts with symptomatic or asymptomatic CDI children there is the risk of intestinal contamination among the health workers who intake antibiotics regardless of contacts closeness and total years of service at the hospital. At the same time, patients without diarrhea and, possibly, health workers of the department can be considered as an additional reservoir of C. difficile.